A prospective randomised study on efficacy of music for decreasing preoperative anxiety in children. Issue 7 (July 2021) - Nguyen, Cynthia V; Alvin, Madeleine; Lee, Carol; George, Darrell; Gilmore, Allison; Tripi, Paul A; Liu, Raymond W
Background: The operating room can be a frightening environment for paediatric patients. This study investigated whether music medicine can mitigate preoperative anxiety in children. Materials and methods: One hundred and fifty children undergoing general anaesthesia were randomised to listen to music of the child's choice, lullaby music or no music before induction. Heart rates were measured in the waiting room, upon first entry into the operating room and just prior to induction. Results: There was no significant difference in average heart rate change from the waiting room to induction in the patient choice, lullaby and control groups. Older age was associated with higher heart rate changes between baseline and entering the operating room. Pharmacologic sedation showed a significant beneficial effect on heart rate change at induction. Conclusion: Use of music medicine in the operating room does not show efficacy to reduce anxiety in children based on heart rate changes.